Pancreaticoportal Fistula in Association with Antiphospholipid Syndrome Presenting as Ascites and Portal System Thrombosis. (2002) - Chang, Li-Hsin; Francoeur, Luc; Schweiger, Franzjosef
Abstract : Fistulous communication between the pancreas and the portal venous system is extremely rare and is usually a complication of chronic pancreatitis or pancreatic pseudocysts. A patient who presented with abdominal pain and ascites secondary to a pancreaticoportal fistula and portal system thrombosis is described. The diagnosis was made by endoscopic retrograde cholangiopancreatography and confirmed by immediate postprocedure computed tomographic scanning. Laboratory studies identified concomitant antiphospholipid syndrome. The patient responded favourably to supportive medical therapy.